Socio-Ecological Responsibility Using Triple Bottom Line Method Perspective of Mamayu Hayuning Bawana - Jayana, Nur Kholis Perwita; Maharani, Satia Nur; Sudarto, Triadi Agung (Journal of Applied Business, Taxation and Economics Research, 2024)
This research explores the application of the Triple Bottom Line (TBL) concept and Socio-Ecological Responsibility from the perspective of Mamayu Hayuning Bawana (MHB) at Unisma Islamic Hospital Malang. Facing the complex challenges of life, especially in the healthcare sector, companies need to consider social, economic, and environmental aspects in a balanced manner. Unisma Islamic Hospital Malang demonstrates a commitment to TBL with a focus on Profit, People, and Planet. This is reflected in efficient financial management, improved access to healthcare services, proper medical waste management, and the adoption of green technology. The Mamayu Hayuning Bawana concept is also applied, emphasizing harmony between humans, nature, and the divine. The implementation of TBL and Mamayu Hayuning Bawana aims to create a balance between economic needs, social welfare, and environmental sustainability. The Islamic Hospital of the University of Islam Malang (RSI Unisma) has successfully achieved harmony between economic growth, social concern, and environmental preservation, replacing competition with harmonious synergy. This research contributes to understanding sustainability practices in the healthcare sector and encourages other companies to adopt TBL for socio-ecological sustainability. Future studies can focus on other industries, develop more comprehensive impact measurement methods, and involve the community in decision-making processes.